Factors influencing customer purchase decision - Jagajeevanrao, L; Susmitha, V; Pavansahitya, R; Sai Lakshmi, G (International Journal of Engineering and Technology, 2018)
Even though it seems enthusiastic for finding out the customer purchase decision but it is not an easy task. Since there is a huge amount of variation and updating in customer purchasing ways such as online purchasing so in order to evaluate and identify factors research has been started on identifying the factors that cause and grab attention for customer purchase. Some of the factors are customer reviews, privacy, social media, fast delivery, spare shipping, the cheapest price, merchandise and information quality, easy return and a wide option. The aim of this report is to look at the elements influencing the online shopping by the consumers. This is answered by researching the elements that promote consumers to browse online through analysis.Â